Pengaruh Word of mouth, Biaya Pendidikan Dan Fasilitas Madrasah Diniyah Terhadap Keputusan Wali Santri Memilih Madrasah Diniyah (Studi Kasus Pada Wali Santri Madrasah Diniyah Masjid Agung An-Nuur Kota Batu) - Nur Halizah, Sania Putri; Nurhajati, Nurhajati; Amin, Muhammad Sirojuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The selection of a diniyah madrasah (Islamic educational institution) for children involves multidimensional considerations from guardians, including social, economic, and infrastructural factors. This study aims to analyze the influence of Word of mouth (WOM), Education Costs, and Facilities on the decision-making of guardians at Madrasah Diniyah Masjid Agung An-Nuur in Batu City. A quantitative method was employed, with primary data collected through questionnaires distributed to 63 guardians as the research sample. Data were analyzed using multiple regression in IBM SPSS. The results indicate: (1) WOM has a significant partial influence on the selection decision; (2) Education Costs Facilities show no significant individual effects; (3) Collectively, the three variables account for 64.7% of the decision variability. These findings suggest that social recommendations (WOM) dominate the decision-making process, while financial and physical infrastructure considerations are less critical in this religious community context. The study underscores the importance of community-based communication strategies to enhance the competitiveness of diniyah madrasahs. Keywords: : Word of mouth, Education Costs, Facilities, Decision-Making, Diniyah Madrasah